Beyond Reproach: Navigating Usage, Detection, and Future Pathways of AI in Education - Rahul Kumar (Brock University, 2024)
This essay critiques the emphasis on detecting artificial intelligence (AI) usage in student submissions and advocates for a shift towards the meaningful integration of AI in education. Citing data from Turnitin, it highlights the significant yet understated prevalence of AI in academic work. The discussion underscores the ideological, detection, and moral challenges associated with AI in education, arguing for a reconceptualization of assessment and pedagogy to accommodate AI tools ethically and effectively. It calls for collaborative efforts to redesign curricula and assessments, ensuring educators and students are equipped to navigate the evolving educational landscape. The essay concludes by emphasizing the necessity of preparing graduates for a future in which AI plays a central role in learning and professional practice. Keywords: AI usage detection, ethical AI integration, academic integrity, future of AI in education